Out-of-pocket payments and catastrophic expenditures due to traffic injuries in Ouagadougou, Burkina Faso - Petitfour, Laurène; Bonnet, Emmanuel; Mathevet, Isadora; Nikiema, Aude; Ridde, Valéry (Health economics review, 2021)
To estimate the out-of-pocket expenditures linked to Road Traffic Injuries in Ouagadougou, Burkina Faso, as well as the prevalence of catastrophic expenditures among those out-of-pocket payments, and to identify the socio-economic determinants of catastrophic expenditures due to Road Traffic Injuries.
Gesehen am 27.01.2022
Keywords: Aufsatz in Zeitschrift